Cultural Practice of "Ngelawar" and Its Influence on the Spirit of Mutual Cooperation in Balinese Adolescents - Anak Agung Ayu Dewi Sutyaningsih; Sri Endang Lestari; I Putu Eka Sudarsana; Bunga Mustikaa; I Gede Budiarta; Haris Nursyah Arifin; I Wayan Treman; Dwi Sunarti Puspitasari (Mimbar Ilmu, 2026)
The rapid development of modernization and globalization has influenced adolescents’ social behavior, including the decline of collective values such as mutual cooperation and social responsibility. Traditional cultural practices can serve as an important medium for strengthening these values among younger generations. This study aims to analyze the role of ngelawar culture in shaping mutual cooperation behavior among adolescents from social, cultural, and religious perspectives. This research employed a qualitative approach using literature review and semi-structured interviews. The participants involved traditional leaders, religious leaders, parents, adolescents, and academics who understand the implementation of ngelawar traditions. Data were collected through document analysis and interviews and were analyzed using thematic analysis. The findings reveal that ngelawar functions as a medium for transmitting values of togetherness, solidarity, collective responsibility, and cultural identity across generations. Adolescents’ involvement in ngelawar not only develops practical skills but also strengthens spiritual awareness through participation in traditional and religious ceremonies. In addition, ngelawar reinforces social cohesion by creating intergenerational interaction within the community. The study concludes that ngelawar has strategic potential as a medium for character education, cultural preservation, and strengthening youth identity in the era of globalization.